2012
DOI: 10.1051/0004-6361/201116433
|View full text |Cite
|
Sign up to set email alerts
|

Supernovae without host galaxies?

Abstract: Context. A remarkable fraction of supernovae (SNe) have no obvious host galaxy. Two possible explanations are that (i) the host galaxy is simply not detected within the sensitivity of the available data or that (ii) the progenitor is a hypervelocity star that has escaped its parent galaxy. Aims. We use the Type IIb SN 2009Z as a prototype of case (i), an example of how a very faint (here low surface brightness; LSB) galaxy can be discovered via the observation of a seemingly host-less SN. By identifying and st… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 65 publications
0
12
1
Order By: Relevance
“…"Hostless" events are designated separately. For CCSNe these "hostless" events probably do have low-luminosity, coincident hosts fainter than the SDSS detection threshold (e.g., Zinn et al 2012). For most "hostless" SNeIa we anticipate that there is no coincident host and the progenitor has traveled a sufficient distance from the galaxy in which the system formed such that there is no probabilistically secure association, although it is possible that a few may have undetected low-luminosity, coincident hosts (Strolger et al 2002).…”
Section: Host-galaxy Propertiesmentioning
confidence: 98%
“…"Hostless" events are designated separately. For CCSNe these "hostless" events probably do have low-luminosity, coincident hosts fainter than the SDSS detection threshold (e.g., Zinn et al 2012). For most "hostless" SNeIa we anticipate that there is no coincident host and the progenitor has traveled a sufficient distance from the galaxy in which the system formed such that there is no probabilistically secure association, although it is possible that a few may have undetected low-luminosity, coincident hosts (Strolger et al 2002).…”
Section: Host-galaxy Propertiesmentioning
confidence: 98%
“…Lines of constant mean surface brightness are shown as dashed black lines. available to Zinn et al (2012) (20 min exposures on an 8.2m mirror compared to 1 min and 5 min exposures on 2.5and 3.5-m mirrors, respectively). This is particularly evident in Figure 10, where the HSC-SSP image of LSBG-729 reveals spiral structure and compact regions of star formation, whereas only its central region is marginally visible in the SDSS image.…”
Section: A Lsb Supernova Hostmentioning
confidence: 99%
“…Impey & Bothun (1997). Zinn et al (2011) showed that because of the type of explosion (IIb, which require progenitor masses of at least 20 M , see Heger et al 2003), high-mass star formation must also occur in these extremely faint galaxies, which contradicts our current understanding of LSBs. Constraining the star formation history of SN 2009Z's host galaxy, they concluded 1.…”
Section: Introductionmentioning
confidence: 73%
“…In an accompanying paper (Zinn et al 2011), we analyzed the host galaxy of SN 2009Z, which was classified as a low surface brightness (LSB) galaxy. Those galaxies are particularly hard to observe because of their low surface brightness μ B > 23 mag arcsec −2 as defined by e.g.…”
Section: Introductionmentioning
confidence: 99%